Decision intelligence : transform your team and organization with AI - driven decision - making - Heilig, Thorsten; Scheer, Ilhan (Hoboken, New Jersey : Wiley, 2024)
"Decision Intelligence is for all leaders, decision makers, and people who are looking to incorporate data and AI-based approaches into their decision-making processes. Applicable to both the tech sector and more traditional industries, this book explores how data-driven and AI-based decision-making is changing industries, organizations, and individuals on a fundamental level. It's a digestible read for people at any part in the decision-making journey and breaks down new technology, approaches, and algorithms to bridge the gap between behavioral science, data science, and technological innovation. Decision Intelligence will cover key topics in the field: -Introduction to decision intelligence: why traditional approaches to decision-making must change and why they must change now . -Comparison of complex vs. dynamic environments and evolution from analytics (linear and static) to process mining and RPA (repeatable processes) -Three levels of decision intelligence: support, augment, automate (with examples for each) -Decision intelligence in organizations, including agile transformation, transparent organizational culture, and new ways of decision-making at a corporate level -Decision intelligence in teams and individuals. Explores fundamental psychological change, leadership, and psychological safety. Empowered individuals create highly functional teams."--
Includes bibliographical references and index.
Keywords: Decision making; Artificial intelligence